ISLAMIC BUSINESS ETHICS YUSUF AL-QARDHAWI'S PERSPECTIVE - Nurul A'yun (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mmojokerto, 2024)
This research aims to analyze and understand business ethics from the perspective of Yusuf al-Qardhawi, a leading Islamic cleric and scholar. The focus of the research is to identify the basic principles of business ethics proposed by al-Qardhawi, as well as how these principles are applied in modern business practices. The research method used is qualitative research with a descriptive-analytical approach. Data was collected through literature studies which included the written works of Yusuf al-Qardhawi and other relevant secondary sources. Data analysis was carried out by examining main concepts such as justice, honesty, trust, prohibition of usury and gharar, and social responsibility in the context of Islamic business ethics. It is hoped that the research results will provide in-depth insight into how Islamic ethical values ​​can be integrated into daily business practices, as well as contribute to the development of Islamic business ethics theory and practice. Keywords: business ethics, Yusuf al-Qardhawi